AKIBAT HUKUM ATAS WANPRESTASI DALAM PERJANJIAN UTANG PIUTANG (STUDI KASUS PUTUSAN PENGADILAN NEGERI INDRAMAYU NOMOR 1/PDT.G/2021/PN IDM) - Berhimpon, Eliezar; Ardiansyah (FOCUS, 2024)
In the business world, contractual relationships often involve agreements between two parties, each of whom has obligations or "performances" to fulfill. However, issues may arise where one party fails to fulfill their obligations, which is referred to as breach of contract or "default" (wanprestasi). This paper aims to address two key questions: what are the legal consequences of default in a debt agreement, and how does the court analyze the reasoning behind the decision in case number 1/Pdt.G/2021/PN Idm? The research method employed is normative legal research. The study's findings indicate that the legal consequence of default in a debt agreement is a claim for damages. According to Article 1243 of the Indonesian Civil Code (KUHPerdata), damages may include costs, losses, and interest. To claim damages, a prior demand for performance or formal notice (somasi) is generally required, except in certain circumstances where a warning is unnecessary. In the court decision number 1/Pdt.G/2021/PN Idm, the judge concluded that the defendant failed to meet their obligation to repay the debt to the plaintiff as agreed. The default occurred when the defendant did not pay the remaining debt of IDR 90,000,000 (ninety million rupiah) with an interest rate of 3% on the principal debt of IDR 475,000,000 (four hundred seventy-five million rupiah). According to the concept of default, three conditions can determine whether a party has breached the contract: 1) not fulfilling the obligation at all, 2) fulfilling the obligation but poorly or incorrectly, and 3) fulfilling the obligation but not on time.